Banks' bail-in and the new banking regulation: An EU event study - Bellia Mario; Maccaferri Sara (Publications Office of the European Union, 2020)
The purpose of the study is to estimate the short term reaction of equity and CDS prices of a sample of European banks to various events and announcements, such as bail-ins, recapitalisations, and the proposal and final agreement of the EU reform package of prudential and resolution rules in banking ("banking package"). This study replicates and expand Schäfer et al. (2017) to include more recent EU events, such as the resolution of Banco Popular and the further tightening of EU prudential and resolution rules in 2019. Overall, our analysis shows the most recent events did not seem to trigger abnormal reactions in bank funding markets after bank prudential and resolution reforms were implemented in the EU in 2016. An exception is the 2018 Council agreement on its general approach to the proposed banking package. While the 2016 and 2019 reforms of EU prudential and resolution rules seem to have increased perceived probabilities of bail-in, the latter seem not to be affected significantly by more recent individual cases.
Keywords: 330